2020
DOI: 10.1109/ms.2020.2985621
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Industrial Practice in Artificial Intelligence Ethics

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 9 publications
0
45
0
Order By: Relevance
“…For instance, job automation and the substantial displacement of workforces induced by AI has triggered considerable stress for healthcare practitioners (Davenport & Kalakota, 2019). Vakkuri et al (2020) point out that the public is becoming aware of the ethical implications of AI technology, relating to, for example, the lack of data structure (Panch et al, 2019), ethical concerns over its unintended impacts (Peters et al, 2020), and human acceptance of machines (Anderson & Anderson, 2007). Hospitals face not only the challenges of understanding how AI can be deployed responsibly, but also of whether their engagement with AI can subsequently generate positive outcomes such as favourable attitudes, greater satisfaction, and higher usage intentions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, job automation and the substantial displacement of workforces induced by AI has triggered considerable stress for healthcare practitioners (Davenport & Kalakota, 2019). Vakkuri et al (2020) point out that the public is becoming aware of the ethical implications of AI technology, relating to, for example, the lack of data structure (Panch et al, 2019), ethical concerns over its unintended impacts (Peters et al, 2020), and human acceptance of machines (Anderson & Anderson, 2007). Hospitals face not only the challenges of understanding how AI can be deployed responsibly, but also of whether their engagement with AI can subsequently generate positive outcomes such as favourable attitudes, greater satisfaction, and higher usage intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from evaluating ECCOLA, this study provides an initial look into writing ethical user stories. Bridging the gap between research and practice in AI ethics has been a recurring challenge in the area, with companies struggling to implement abstract ethical guidelines in practice [2,3]. User stories can help us bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McNamara et al [9] replicated a prior behavior ethics study, and found out that explicitly instructing participants to consider the ACM Code of Ethics in relation to the impacts of their software development decision-making had no influence on actual ethical decision-making itself. In the field of AI ethics, [2] discovered a gap between research and practice regarding the ways in which AI ethics are implemented. While on the one hand, AI ethics are discussed in academic circles, on the other hand, discussions had not carried over to industrial application.…”
Section: Implementing Ethics Into Software Developmentmentioning
confidence: 99%
See 2 more Smart Citations